The Democratic Simulation of the Public Space and Its Complex Human Relations - Ponce, Wendy Montes (Cultural and religious studies, 2018)
The public space is currently the product of a simulation of democracy, the subject of the present investigation. In the phenomenon, social aspects intervene that gestate labor, religious and political activities. The observation of urban behavior in historic centers was handled through the deductive method observing permitted or prohibitive areas of commercialization in the Historic Center of Oaxaca; it shows that it was determined by the reproduction of the urban simulation. The purpose was focused on the exploration of spatial utility and the normative models of urban practices and practices. The results revealed the public space is the product of negotiations that exhibit multiple inequalities: social strata, division of labor, political interests, religious and cultural expressions. Spatial projections are of: expropriation, distribution, donation, and resignation; from a domestic to industrial scale. The democratic simulation and its complex human relations multiplied the creeds and collective rituals, the proliferation of non-legal business and the dispute of the public space. It is concluded that those who administer and enforce civic policies and urban rules should promote solutions for coexistence; as a formative and attitudinal issue in the space that belongs to all of us.